Evaluation of Hoffman and Xia plasticity models against bi-axial tension experiments of planar fiber network materials. (1st March 2022) - Alzweighi, Mossab; Mansour, Rami; Tryding, Johan; Kulachenko, Artem
Abstract: The anisotropic properties and pressure sensitivity are intrinsic features of the constitutive response of fiber network materials. Although advanced models have been developed to simulate the complex response of fibrous materials, the lack of comparative studies may lead to a dubiety regarding the selection of a suitable method. In this study, the pressure-sensitive Hoffman yield criterion and the Xia model are implemented for the plane stress case to simulate the mechanical response under a bi-axial loading state. The performance of both models is experimentally assessed by comparison to bi-axial tests on cruciform-shaped specimens loaded in different directions with respect to the material principal directions. The comparison with the experimentally measured forces shows the ability of the Hoffman model as well as the Xia model with shape parameter k ≤ 2 to adequately predict the material response. However, this study demonstrates that the Xia model consistently presents a stiffer bi-axial response when k ≥ 3 compared to the Hoffman model. This result highlights the importance of calibrating the shape parameter k for the Xia model using a bi-axial test, which can be a cumbersome task. Also, for the same tension-compression response, the Hill criterion as a special case of the Hoffman model presents a good ability to simulate the mechanical response of the material for bi-axial conditions. Furthermore, in terms of stability criteria, the Xia model is unconditionally convex while the convexity of the Hoffman model is a function of the orthotropic plastic matrix. This study not only assesses the prediction capabilities of the two models, but also gives an insight into the selection of an appropriate constitutive model for material characterization and simulation of fibrous materials. The UMAT implementations of both models which are not available in commercial software and the calibration tool of the Xia model are shared with open-source along with this work. Highlights: The implementations of Hoffman and Xia models are presented along with the shared UMAT implementations. The performance of both models is assessed with the biaxial tension experimental measurements. To accurately calibrate the Xia model a biaxial test is required. Xia is unconditionally convex while the convexity of Hoffman is conditional. Neglecting the asymmetric tension-compression response, Hill criterion shows a good agreement with the bi-axial tension experiment.